INVESTIGATION OF THE CORROSION BEHAVIOUR OF ALUMINIUM ALLOY IN SELECTED ENVIRONMENTS (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2019)
The corrosion behaviour of aluminium alloy EN AW-2011 was investigated in selected environments of various electrolytes using gravimetric technique. The results showed that, under the conditions employed in the present work, the corrosion rate of this alloy depends on the specific ions present in solution. The corrosion resistance of aluminium alloy EN AW-2011 is higher in solutions of acids and salts containing sulfate and nitrate ions than in these consisting chloride ions.